2021
DOI: 10.1111/papt.12332
|View full text |Cite
|
Sign up to set email alerts
|

Review of the current empirical literature on using videoconferencing to deliver individual psychotherapies to adults with mental health problems

Abstract: Purpose. The COVID-19 pandemic has resulted in a widespread adoption of videoconferencing as a communication medium in mental health service delivery. This review considers the empirical literature to date on using videoconferencing to deliver psychological therapy to adults presenting with mental health problems.Method. Papers were identified via search of relevant databases. Quantitative and qualitative data were extracted and synthesized on uptake, feasibility, outcomes, and participant and therapist experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 91 publications
(242 reference statements)
6
68
0
4
Order By: Relevance
“…This also allowed for opportunities presented by telehealth to be capitalized upon, such as convenience of access and appointments being less rushed. In line with other reports of the use of telehealth [1][2][3][4][5][6][7], using more remote communication channels sometimes overcame discomfort associated with in-person interaction. There also appeared to be a potential to increase the power and control the client had within the relationship through these choices, which may be especially important in this often-disempowered client group.…”
Section: Principal Findingssupporting
confidence: 80%
See 3 more Smart Citations
“…This also allowed for opportunities presented by telehealth to be capitalized upon, such as convenience of access and appointments being less rushed. In line with other reports of the use of telehealth [1][2][3][4][5][6][7], using more remote communication channels sometimes overcame discomfort associated with in-person interaction. There also appeared to be a potential to increase the power and control the client had within the relationship through these choices, which may be especially important in this often-disempowered client group.…”
Section: Principal Findingssupporting
confidence: 80%
“…In common with previous telehealth implementations [5,7,17], service users indicated a need to adapt to new ways of interacting with services, and workers expressed concerns that technical difficulties and a lack of in-person presence would interfere with maintaining an effective helping relationship. We found that during this pandemic, when telehealth was typically the only way to receive psychosocial support, service users were generally willing to adapt, and adjustment to a new service delivery model could be navigated for most.…”
Section: Principal Findingsmentioning
confidence: 93%
See 2 more Smart Citations
“…Whilst early research into the effectiveness of remote therapies is promising, direct comparisons with in-person therapy are still scarce, and views of service users, carers and staff are mixed, with some concerned about being digitally excluded and the loss of a therapeutic "safe space" (Liberati et al, 2021). A recent review of the literature concluded that studies of the use of videoconferencing for severe mental illness are currently lacking (Thomas et al, 2021) and the impact of the shift toward remote intervention will inevitably be complex, with research needed to identify adverse effects as well as benefits.…”
Section: Introductionmentioning
confidence: 99%